Improving fabrication and application of zach phase plates for phase-contrast transmission electron microscopy - Hettler, Simon Josef; Frindt, Nicole; Schröder, Rasmus R. (Microscopy and microanalysis, 2012)
Zach phase plates (PPs) are promising devices to enhance phase contrast in transmission electron microscopy. The Zach PP shifts the phase of the zero-order beam by a strongly localized inhomogeneous electrostatic potential in the back focal plane of the objective lens. We present substantial improvements of the Zach PP, which overcome previous limitations. The implementation of a microstructured heating device significantly reduces contamination and charging of the PP structure and extends its lifetime. An improved production process allows fabricating PPs with reduced dimensions resulting in lower cut-on frequencies as revealed by simulations of the electrostatic potential. Phase contrast with inversion of PbSe nanoparticles is demonstrated in a standard transmission electron microscope with LaB6 cathode by applying different voltages.